Role of Lignin in Moisture Interactions of Cellulose Microfibril Structures in Wood - Aleksi Zitting; Antti Paajanen; Michael Altgen; Lauri Rautkari; Paavo A. Penttilä (Small Structures)
Wood is a complex, multi‐component material with a variety of applications. The properties of wood are especially sensitive to its moisture content and comprehending wood–water interactions is thus paramount. Understanding of the moisture interactions of the wood polysaccharide components, cellulose microfibrils and hemicelluloses, is improving. However, the role of lignin remains less clear. In this work, X‐ray scattering measurements were carried out on delignified spruce undergoing a desorption‐adsorption cycle, and the results were compared to previous data from untreated wood. In addition, a molecular model of the cell wall nanostructure, including the main chemical components, was used to support the experimental results. Based on the small‐angle scattering, delignification affects the arrangement of cellulose microfibrils in the cell wall by increasing their packing distance. Wide‐angle scattering shows that delignification has no substantial effect on the cellulose crystal structure and how it changes with moisture. Both the scattering results and simulations suggest that lignin is a passive, rather than an active participant in the moisture response of microfibril bundles in wood cell walls. Small‐angle scattering from fully wet delignified wood reveals a contribution that can be assigned to aligned nanometer scale pores which close during drying.